Etiologi dan Patogenesis Limfangioleiomiomatosis - Yovita Harmiatun (Fakultas Kedokteran Universitas Kristen Indonesia, 2007)
Abstract LAM stands for lymphangioleiomyomatosis is a progressive lung disease which affects women of all races. Usually the disease manifested during their reproductive age. Pathologically, it is characterized by the abnormal proliferation of immature smooth muscle-like cells that grow aberrantly in the lung pulmonary airway, parenchyma, lymphatics, and blood vessels. The relentless growth of LAM cells leads to respiratory failure and death. lymphangioleiomyomatosis lesions are generated by the proliferation of LAM cells with mutations of one of the tuberous sclerosis complex (TSC) genes. LAM is a rare disease and often goes misdiagnosed as asthma, emphysema, and pulmonary bronchitis. Recent studies indicate that LAM cells can migrate or metastasize to form new lesions in multiple organs. Although they show amorphologically benign appearance. Scientists estimate that there could be 300000 LAM patients worldwide. Recent progress has been made in understanding more about pathogenesis of LAM and facilitate the identification of potential therapeutic targets, aimed at abrogating the aberrant cellular proliferation characteristic of LAM. Keywords: lymphuugloleiomyomatosis; progressive lung disease; abnormal proliferation; immature smooth muscle-like cells